Prolonged paralysis following mivacurium administration in a pediatric patient with previously undiagnosed pseudocholinesterase deficiency: a case report - Uzun, Davut D.; Wildenberg, Katharina; Ruping, Fabian; Westhoff, Jens; Schmitt, Felix; Weigand, Markus A.; Živković, Aleksandar (BMC pediatrics, 2025)
BackgroundPseudocholinesterase, an enzyme produced by the liver and abundantly present in plasma, plays a role in the metabolism of neuromuscular blocking agents such as mivacurium. The administration of mivacurium to patients with pseudocholinesterase deficiency during general anesthesia has been associated with the occurrence of prolonged postoperative paralysis, a rare but potentially severe side effect.Case presentationA 24-month-old girl underwent routine, elective minor surgery. The neuromuscular blocking agent mivacurium was used during general anesthesia. Following the procedure, there was no spontaneous recovery of breathing. The peripheral nerve stimulator used to measure neuromuscular relaxation did not elicit any responses. The patient was subsequently transferred to the pediatric intensive care unit, where she was successfully weaned from the ventilator and extubated four hours later. The following day, the child was deemed fit for discharge from the clinic, exhibiting no residual symptoms. A targeted laboratory analysis conducted subsequent to the event revealed a cholinesterase level of 4176 U/l (normal values 4260-12920 U/l), a cholinesterase dibucaine-number of 12 (normal values > 70) and cholinesterase fluoride-number of 29 (normal values 55-60).ConclusionsThis is a case report of pseudocholinesterase deficiency in a 24-month-old child undergoing minor surgery. Quantitative neuromuscular monitoring should be used routinely to recognize prolonged muscle relaxation. If the diagnosis of pseudocholinesterase deficiency is confirmed, the patient should be given information about the disorder, the associated risks, inheritance and the need for testing in other family members.